2014
DOI: 10.3390/children1020134
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Pediatric Pain

Abstract: Chronic pain is a growing problem in children, with prevalence as high as 30.8%. Acupuncture has been found to be useful in many chronic pain conditions, and may be of clinical value in a multidisciplinary treatment program. The basic principles of acupuncture are reviewed, as well as studies exploring basic mechanisms of acupuncture and clinical efficacy. Conditions commonly treated in the pediatric pain clinic, including headache, abdominal pain, fibromyalgia, juvenile arthritis, complex regional pain syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 81 publications
0
23
0
1
Order By: Relevance
“…Other CAM interventions including acupuncture, hypnosis, massage, music therapy, pet therapy, and osteopathic or chiropractic manipulation could be considered as part of the comprehensive pain management program, though randomized controlled trials in pediatrics are limited, particularly for those not involving direct physical touch (hypnosis, music therapy, and pet therapy) [130,150]. Acupuncture can provide benefit and be well tolerated in children as young as 6 years of age with varying pain conditions, including migraines, abdominal pain, fibromyalgia, and CRPS type 1 [151,152]. Intolerance, including anxiety about the acupuncture procedure, may be reduced when combined with hypnosis [152].…”
Section: Complementary and Alternative Medicine (Cam)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other CAM interventions including acupuncture, hypnosis, massage, music therapy, pet therapy, and osteopathic or chiropractic manipulation could be considered as part of the comprehensive pain management program, though randomized controlled trials in pediatrics are limited, particularly for those not involving direct physical touch (hypnosis, music therapy, and pet therapy) [130,150]. Acupuncture can provide benefit and be well tolerated in children as young as 6 years of age with varying pain conditions, including migraines, abdominal pain, fibromyalgia, and CRPS type 1 [151,152]. Intolerance, including anxiety about the acupuncture procedure, may be reduced when combined with hypnosis [152].…”
Section: Complementary and Alternative Medicine (Cam)mentioning
confidence: 99%
“…Intolerance, including anxiety about the acupuncture procedure, may be reduced when combined with hypnosis [152]. For those with concerns regarding needles, noninvasive acupuncture techniques, including transcutaneous electrical acupoint stimulation and laser acupuncture, may be an alternative [151].…”
Section: Complementary and Alternative Medicine (Cam)mentioning
confidence: 99%
“…[19][20][21] A review of the acupuncture literature suggests positive evidence supporting the use of acupuncture for both acute and chronic pain in the pediatric population. 22 While adverse events have been reported, acupuncture is considered safe when performed by properly trained practitioners. 23 Increasingly, CIM is being successfully implemented in pediatric hospital settings globally, 24,25 with findings beginning to point to lessons that can be applied in the implementation of CIM more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of systematic reviews have concluded that additional high-quality trials are needed among children to assess the effectiveness of acustimulation to reduce pain, nausea, and vomiting in general populations, 42,[55][56][57][58][59] as well as in childhood cancer. 29,30,60,61 Trial Objectives/Aims…”
Section: Background and Rationalementioning
confidence: 99%